Ethan Frome - Wharton, Edith, 1862-1937 (Open Road Integrated Media, 2015)
One of literature's keenest social critics, Pulitzer Prize'winning author Edith Wharton weaves a tragic small-town tale of epic proportions in this masterful novella Physically disfigured and trapped in a loveless marriage to a sickly older woman, Ethan Frome is a broken man. He lives a desolate, impoverished life in the town of Starkfield, Massachusetts, bound by an unassailable sense of duty. But long ago, Ethan dreamed of something beyond his bleak and tedious New England existence. Once, he had dared to have hope for the future. Ethan Frome tells the wrenching story of a love destined not to be and a man mired in his own private hell. This ebook has been professionally proofread to ensure accuracy and readability on all devices.